Przepisy o kontrolowanych spółkach zagranicznych (CFC) w świetle międzynarodowego prawa publicznego - Kuźniacki, Błażej (Kwartalnik Prawa Podatkowego, 2015)
This paper concentrates on relations between taxation triggered by controlled foreign companies’ rules and international public law. The purpose of the paper is to answer to the research question: whether and why taxation of a CFC’s income by the State of residence of taxpayers controlling CFC is neither restricted nor unjustified in the light of international public law.